The Effect of Education on Income Inequality in Indonesia - Rahadi Nugroho (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Indonesia underwent an economic recession as a result of the Covid-19 pandemic. This study seeks to assess the degree to which education contributes to income disparity in Indonesia. This research utilizes data acquired from the Central Statistics Agency (BPS). The Gini coefficient measures economic inequality, whereas average years of schooling and participation rates for individuals under 19 and those aged 19-23 assess education. The average years of education did not substantially influence the Gini coefficient. Simultaneously, the engagement rate for individuals aged 19-23 exhibited a beneficial impact. A higher participation rate correlates with a larger income disparity. This supports the idea that educational attainment will enhance inequality to a specific extent.